2022
DOI: 10.1029/2021ja030029
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study of Foreshock Bubbles, Hot Flow Anomalies, and Spontaneous Hot Flow Anomalies and Their Substructures Observed by MMS

Abstract: Ubiquitous throughout the universe, shocks form when a supersonic flow encounters an obstacle and are important particle accelerators through different acceleration mechanisms (e.g., Helder et al., 2012;Lee et al., 2012). On Earth, a bow shock forms when the supermagnetosonic solar wind encounters the magnetosphere. At the quasi-parallel bow shock (where the angle between the shock normal and the interplanetary magnetic field (IMF) is less than 45°), some solar wind particles are reflected by the bow shock and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 70 publications
(191 reference statements)
1
39
1
Order By: Relevance
“…We establish an event list of 411 DHs with Magnetospheric Multiscale 1 (MMS1) in the solar wind from October 2017 to April 2018 and October 2018 to May 2019 (∼15 months). We use the solar wind time intervals from Vu et al (2022) through machine learning and note that the presence of the foreshock region is not a requirement to investigate whether DHs could be solar wind structures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We establish an event list of 411 DHs with Magnetospheric Multiscale 1 (MMS1) in the solar wind from October 2017 to April 2018 and October 2018 to May 2019 (∼15 months). We use the solar wind time intervals from Vu et al (2022) through machine learning and note that the presence of the foreshock region is not a requirement to investigate whether DHs could be solar wind structures.…”
Section: Methodsmentioning
confidence: 99%
“…We use the solar wind time intervals from Vu et al. (2022) through machine learning and note that the presence of the foreshock region is not a requirement to investigate whether DHs could be solar wind structures.…”
Section: Methodsmentioning
confidence: 99%
“…However, the spatial scale of foreshock transients like HFAs is typically a few R E (e.g., Facskó et al., 2009; Lin et al., 2022; Vu et al., 2022), much smaller than the solar wind impulses or shocks. They also have sub‐scale structures with complicated pressure variation inside their core region (e.g., Vu et al., 2022; S. Wang et al., 2012). Therefore, considering their significant pressure variation across a rather small spatial scale, they may result in strong pressure gradients near the magnetopause.…”
Section: Introductionmentioning
confidence: 99%
“…For major magnetopause disturbances, such as those caused by solar wind impulses or shocks, global MHD simulations (e.g., Fujita, Tanaka, Kikuchi, Fujimoto, Hosokawa, & Itonaga, 2003; Fujita, Tanaka, Kikuchi, Fujimoto, & Itonaga, 2003; Keller et al., 2002; Slinker et al., 1999) and observations (e.g., Glassmeier et al., 1989; Moretto et al., 2002; Tian et al., 2016) have shown that the flow vortices are a dominant driver of the associated FACs. However, the spatial scale of foreshock transients like HFAs is typically a few R E (e.g., Facskó et al., 2009; Lin et al., 2022; Vu et al., 2022), much smaller than the solar wind impulses or shocks. They also have sub‐scale structures with complicated pressure variation inside their core region (e.g., Vu et al., 2022; S. Wang et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation